(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The paper examines the literature data on factors affecting the process of fibrogenesis and cirrhosis in chronic viral hepatitis. It is shown that the course of fibrogenesis depends not only on the microorganism and the duration of the infection, but also on the genetic predisposition and characteristics of the macroorganism, the activity of the pathological process, the effects of hepatotoxic agents (primarily ethanol), etc.